PRELIMINARY ASSESSMENT OF THE EFFECTIVENESS OF MOLNUPIRAVIR IN TREATMENT OF COVID-19 PATIENTS IN EASTERN PEOPLE MILITARY HOSPITAL - Phạm , Thị Tuyết Lang; Nguyễn , Thị Huyền; Lê , Thị Thúy Loan; Nguyễn , Thị Ân; Trương , Hoàng Việt; Hà , Phạm Trọng Khang; Nguyễn , Đức Công (Journal of 175 Practical Medicine and Pharmacy, 2023)
Background: The coronavirus (COVID-19) pandemic remains a global burden. Manifestations of the disease range from asymptomatic to respiratory failure, multi-organ failure, and sepsis. Evaluating the effectiveness of antiviral drugs can help to apply in treatment to prevent these dangerous complications. Objective: To determine the effectiveness of molnupiravir in the treatment of patients with mild-moderate COVID-19 at Eastern Military Hospital from October 2021 to December 2021. Methods: Descriptive study, performed on 225 hospitalized patients with mild-moderate COVID-19 whose history, clinical symptoms and COVID-19 virus were investigated. Patients were treated with standard regimen, or standard regimen plus molnupiravir, and viral load was assessed on day 1 and 10. Results: In the 225 study patients, the negative rate for COVID-19 in the standard treatment group was 25%, in the molnupiravir group it was 30.4%. The research showed that molnupiravir reduced the time of viral clearance with p<0,001. In patients who remained positive for COVID-19 on day 10, patients treated with molnupiravir had a lower viral load on day 10 than the standard treatment group (p=0,049). Conclusion: Preliminary assessment of molnupiravir resulted in a significant reduction in viral load in patients with mild-moderate COVID-19.